Technology and the Great Divergence. - Allen, R (Department of Economics (University of Oxford), 2011)
The paper measures productivity growth in seventeen countries in the nineteenth and twentieth centuries. GDP per worker and capital per worker in 1985 US dollars were estimated for 1820, 1850, 1880, 1913, 1939 by using historical national accounts to back cast Penn World Table data for 1965 and 1990. Frontier and econometric production functions are used to measure neutral technical change and local technical. The latter includes concurrent increases in capital per worker and output per worker beyond the highest values achieved. These increases were pioneered by the rich countries of the day. An increase in the capital-labour ratio was usually followed by a half century in which rich countries raised output per worker at that higher ratio. Then the rich countries moved on to a higher capital-ratio, and technical progress ceased at the lower ratio they abandoned. Most of the benefits of technical progress accrued to the rich countries that pioneer it. It is remarkable that countries in 1990 with low capital labour ratios achieved an output per worker that was no higher than countries with the same capital labour ratio in 1820. In the course of the last two hundred years, the rich countries created the production function of the world that defines the growth possibilities of poor countries today.